Symptoms and musculoskeletal diseases in hospital nurses and in a group of university employees: a cross-sectional study. Issue 2 (3rd April 2017) - D'Agostin, Flavia; Negro, Corrado
Abstract : Background . Most studies have shown that nurses have a higher risk of developing musculoskeletal symptoms compared with other occupational groups. Aim . A cross-sectional study was performed to gain more insight into the prevalence rates of musculoskeletal disorders (MSDs) in nurses. Methods . The presence of musculoskeletal symptoms was revealed by personal interviews in a sample of 177 hospital nurses and in a reference group of 185 university employees. Musculoskeletal diseases were based on radiological examinations in all subjects. Results . Lower back pain (61% vs 42.2%) was the most frequently reported symptom, followed by neck pain (48.6% vs 38.4%) and shoulder pain (36.7% vs 25.9%), with a significantly higher prevalence in nurses. Women had about a 2-fold risk of upper limb region and neck pain compared with men. The most common abnormal findings on radiological examinations were disc herniations ( n  = 40). Conclusions . Nurses showed a significantly higher risk of MSDs. Prevalence rates in nurses increased significantly with age. Musculoskeletal symptoms were also common in university employees. This suggests the need for effective intervention strategies involving workers' active participation, in order to improve the process and organization of work and promote a positive psychosocial work environment.